2022
DOI: 10.1182/blood.2020009303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of glycans in platelet and megakaryocyte biology

Abstract: Humans produce and remove 1011 platelets daily to maintain a steady-state platelet count. The production of platelets by bone marrow megakaryocytes and their removal from the blood circulation are tightly regulated mechanisms, and abnormalities in both processes can result in thrombocytopenia (low platelet count) or thrombocytosis (high platelet count), often associated with the risk of bleeding or overt thrombus formation, respectively. This review focuses on the role of glycans, also known as carbohydrates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…O- Glycosylation is known to play an important regulatory role in cellular function; however, the majority of platelet studies have focused on the role of N-glycans and O- sialic acids in platelet production and clearance ( 68 , 69 ). Importantly, defective O- glycosylation of platelet proteins results in a bleeding phenotype ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…O- Glycosylation is known to play an important regulatory role in cellular function; however, the majority of platelet studies have focused on the role of N-glycans and O- sialic acids in platelet production and clearance ( 68 , 69 ). Importantly, defective O- glycosylation of platelet proteins results in a bleeding phenotype ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…O-glycosylation is known to play an important regulatory role in cellular function, however, the majority of platelet studies have focused on the role of N-glycans and O-sialic acids in platelet production and clearance 48,49 . Defective O-glycosylation of platelet proteins results in a bleeding phenotype 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about the expression and role of GAGs in the bone marrow and their relevance for the regulation of megakaryocyte functions is rapidly growing, as recently reviewed by Falet et al. [ 27 ] Several studies reported that heparin, heparan sulfate, dermatan sulfate, chondroitin sulfate, and hyaluronic acid stimulate megakaryopoiesis [ 27 ]. Perlecan, a heparan sulfate proteoglycan, is abundantly expressed in the bone marrow, where it regulates megakaryocyte maturation and guides proplatelet formation in the lumen of sinusoidal blood vessels through binding to the G6b-B receptor [ 28 ].…”
Section: The Thrombopoietic Bone Marrow Microenvironment In...mentioning
confidence: 99%